Model of Family Farming... Diversifying rice to vegetable cultivation - Panwar, A S (Indian Horticulture, 2015)
He is a source of inspiration to not only to his villagers but also nearby villagers, who have adopted the technology for income and employment generation. The whole village has started growing vegetables on raised beds after harvest of rice in lowland area. Under the family farming concept production of vegetables on raised beds and their integration with livestock has set up an example of increasing income from limited resources.